Analisis Penggunaan Beberapa Jenis Busi dan Remap Ecu Terhadap Emisi Gas Buang pada Sepeda Motor 4 Tak - Fikri, Muhammad; Sugiarto, Toto (Green Publisher Indonesia, 2024)
The increase in the number of motor vehicles in Indonesia has a significant impact on increasing exhaust emissions that contribute to air pollution. One way to reduce these emissions is through optimizing the combustion process by using variable spark plugs and remapping the ECU (Electronic Control Unit). This study aims to analyze the effect of the use of standard, platinum, and iridium spark plugs, as well as ECU remap at 5° and 10° ignition angles on the exhaust emissions of Vario 125 cc motorcycles. The research method used is an experiment with a pre-test and post-test research design. The test was carried out on three spark plug variations (standard, platinum and iridium) with ignition at angles of 5° and 10°. The testing process involves measuring exhaust emissions, specifically carbon monoxide (CO) and hydrocarbons (HC), at four engine rev levels (rpm) of 1500, 2000, 2500, and 3000. The data was obtained using a gas analyzer and analyzed using mean statistics and percentage of change. The results showed that the use of platinum and iridium spark plugs significantly reduced CO and HC emissions compared to standard spark plugs. At 10° ignition with an iridium spark plug, the largest difference in CO was recorded at 2500 rpm with 23.12%, while the highest HC difference was at 2000 rpm with 37.67%. Platinum spark plugs also provide quite good results with consistent reductions in CO and HC emissions. Remap ECUs with an ignition angle of 10° have proven to be more effective in reducing exhaust emissions compared to 5° ignition.